Medicinal Plants for Mitigating Pain and Inflammatory-Related Conditions: An Appraisal of Ethnobotanical Uses and Patterns in South Africa - Aremu, Adeyemi O.; Pendota, Srinivasa C. (Frontiers in Pharmacology, 2021)
In South Africa, traditional medicine remains the first point of call for a significant proportion of the population seeking primary healthcare needs. This is particularly important for treating common conditions including pain and inflammation which are often associated with many disease conditions. This review focuses on the analysis of the trend and pattern of plants used for mitigating pain and inflammatory-related conditions in South African folk medicine. An extensive search was conducted using various scientific databases and popular ethnobotanical literature focusing on South African ethnobotany. Based on the systematic analysis, 38 sources were selected to generate the inventory of 495 plants from 99 families that are considered as remedies for pain and inflammatory-related conditions (e.g., headache, toothache, backache, menstrual pain, and rheumatism) among different ethnic groups in South Africa. The majority (55%) of the 38 studies were recorded in three provinces, namely, KwaZulu-Natal, Limpopo, and Western Cape. In terms of the number of mentions, the most popular plants used for pain and inflammatory-related conditions in South Africa were Ricinus communis L. (10), Aloe ferox Mill. (8), Pentanisia prunelloides subsp. latifolia (Hochst.) Verdc. (8), Dodonaea viscosa Jacq var. angustifolia (L.f) Benth. (8), (L.) W.T.Aiton. (7) Ruta graveolens L. (7), and Solanum aculeastrum Dunal. (7). The top five plant families represented were Asteraceae (13%), Fabaceae (8%), Apocynaceae (4.3%), Asparagaceae (4%), and Lamiaceae (4%). An estimated 54% of the recorded plants were woody (trees and shrubs) in nature, while the leaves (27%) and roots (25%) were the most dominant plant parts. The use of plants for alleviating pain and inflammatory-related conditions remains popular in South African folk medicine. The lagging ethnobotanical information from provinces such as North West, Gauteng, and Free State remains a gap that needs to be pursued meticulously in order to have a complete country-wide database.